RUSSIA DOESN’T SUPPORT «SHALE REVOLUTION» - S. S. Zhiltsov; A. Sh. Nogmova (Проблемы постсоветского пространства, 2017)
Growth of volumes of production of shale gas in the USA compelled Russia to pay attention to this type of resourses. The interest to shale gas in Russia was limited to discussions at the level of experts and reflection of importance of this problem in statements of politicians. In the next years in Russia don't plan production of shale gas commercially. It is connected with existence in Russia of considerable reserves of traditional natural gas, absence of exact data of reserves of shale gas, high costs of production, and also environmental risks which accompany development of fields of shale gas.